Marvels and Dreams. Notes on Stefan George - Fronzi, Giacomo (Aesthetica Preprint, 2021)
Together with Hugo von Hofmannsthal and Rainer Maria Rilke, Stefan George was one of the most important German poets of the early 20th century. Described by Rilke as a “Master” and by Hofmannsthal as “the great poet of our time”, George contributed to the revival of poetry in Germany. His role in German cultural and political history was as important as it was controversial, and his poetic collections include “esoteric” tendencies, reflections on political events and philosophical instances. Unlike other great poets of his time, and despite the attention he received from philosophers, poets and composers in the first half of the 20th century, George has often been overlooked in critical studies. In this paper, some of the characteristics of his poetry are examined by contextualizing George’s poetic figure in the framework of one of the most fascinating and complex cultural, literary, political, and philosophical landscapes in the history of the twentieth century.